Classification of headache disorders - Sacco, Sara (Henry Stewart Talks, 2023)
International classification of headache disorders, Patient history, Primary headaches, Secondary headaches, Painful cranial neuropathies and other facial pain, Migraine with and without aura, Tension-type headaches, Trigeminal autonomic cephalalgias, Headache attributed to infection